Effects of oral zinc supplementation in the prevention of community-acquired pneumonia in colombian children: an economic evaluation - Diana Guerrero Patiño; Mery Ann Rojano Canchila; Jefferson Antonio Buendía (BMC Public Health)
Abstract Introduction  Oral zinc supplementation is a well-known intervention, widely used to prevent infectious diseases. However, it is also necessary to demonstrate that it achieves the maximum benefit at the lowest possible cost in pneumonia in children, particularly in low- and middle-income countries. This economic evaluation aims to estimate the cost-utility and cost-effectiveness of zinc supplementation for the prevention of community-acquired pneumonia in children aged 1 to 6 years in Colombia.  Materials and methods Using the decision tree analysis, we estimated the expected benefits and costs of zinc supplementation versus no supplementation based on data on effectiveness and cost previously published in Colombia. The perspective of the present economic evaluation is the perspective of society with a time horizon of 1 year. Results The net monetary benefit (NMB) with oral zinc supplementation was US$ 5,063.3 (95% UI: 5,061–5,065), compared to US$ 5,062.6 (95% UI: 5,060–5,064) without supplementation. The estimated cost effectiveness ratio was U$ 4 873 per QALY and U$ 10 324 per year lived gained. In the probabilistic sensitivity analysis, oral zinc supplementation was the most cost-effective therapy in the 53.4% of replications at willingness-to-pay (WTP) of U$ 5180 values. Conclusion In conclusion, oral zinc supplementation in children aged 1 to 6 years in Colombia appears to be a potentially cost-effective strategy for the prevention of community-acquired pneumonia compared to non-supplementation. These findings should be interpreted with caution given the small absolute difference in benefits and the marginal incremental net monetary benefit observed. This result becomes an input for the construction of public health policies aimed at reducing the burden of disease generated by respiratory infections in Colombia, as well as serving as an example and motivation to assess the cost and utility of these strategies in other developing and developed countries.